PROBLEMATIQUE DU DEVELOPPEMENT DES INDUSTRIES AGROALIMENTAIRES EN ALGERIE - Khelifa, Horri; Azeddine, Dahane; Mhamed, Maatoug (European Scientific Journal, ESJ, 2015)
Food processing industry in algeria constitutes an important link of the national industrial network. This is because it plays an important role in the country’s economy. In fact, it takes part efficiently and provides a sustainable way in improving the GDP, and in reducing the rate of unemployment in a country. For this purpose, the government has accorded a special attention to its development during the last decade. Therefore, through the adoption and the concrete application of different policies and strategies, this industry aims at positioning again the driving force of this sector, as well as the economic sphere of the country. Hence, this was first achieved by a better integration of the upstream and downstream sector for these activities. Also, it was followed by a qualitative and quantitative improvement of its competitiveness facing an increasingly fierce competition.